Weekly English tips by the English Language Club UiTMCPP / Noor Azli Affendy Lee, Nur Ilianis Adnan and Muhammad Aiman Abdul Halim - Affendy Lee, Noor Azli; Adnan, Nur Ilianis; Abdul Halim, Muhammad Aiman (Academy of Language Studies, 2022)
In the current October 2021 – February 2022 semester, the English Language Club (ELC) decided to share some weekly English tips on our Instagram and newly-created Facebook pages to encourage our followers and general viewers to learn and practise the English language. Throughout the semester, on Mondays, the executive member in charge of promotion (Promo AJK) will be posting the Idiom of the Week, a 1-page post on a chosen idiom complete with illustration, meaning and example. On Thursdays, the Promo AJK will be posting General English Tips, a multiple-page post involving interesting general English language improvement tips.